2022
DOI: 10.3390/plants11030445
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Physiological Analysis of Rootstock Types and Silicon Affecting Cold Tolerance of Cucumber Seedlings

Abstract: Cucumbers grafted on rootstocks with different wax-removing abilities show varying levels of cold tolerance. The content of pericarp wax powder correlates with its silicon-metabolizing capacity, and rootstock grafting can alter not only the cold tolerance but also the silicon-metabolizing capacity of the scion. The molecular mechanisms responsible for resistance due to rootstocks and silicon and the pathway that affects cold tolerance, however, remain poorly understood. Therefore, we performed physiological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Grafting is one of the most commonly used techniques in vegetable crop production, which can improve stress tolerance, yield, and quality of vegetables ( Shi et al, 2019 ; Wei et al, 2019 ; Darre et al, 2022 ). In recent years, many studies have shown that the cold tolerance of vegetable crops can be improved by grafting onto tolerant rootstock by maintaining higher photosynthesis, enhancing antioxidant activity to scavenge excess reactive oxygen species (ROS) ( Xu et al, 2016 ; Lu J. et al, 2022 ; Luan et al, 2022 ), but information regarding the molecular mechanism of grafting in increasing cold tolerance remains largely unknown. In this study, we found that cucumber seedlings grafted onto figleaf gourd significantly increased the tolerance to cold stress through promoting the accumulation of ABA to induce the expression of WRKY41 and WRKY46 , which further activated the expression of miR396b-5b to target cleavage of TPR .…”
Section: Discussionmentioning
confidence: 99%
“…Grafting is one of the most commonly used techniques in vegetable crop production, which can improve stress tolerance, yield, and quality of vegetables ( Shi et al, 2019 ; Wei et al, 2019 ; Darre et al, 2022 ). In recent years, many studies have shown that the cold tolerance of vegetable crops can be improved by grafting onto tolerant rootstock by maintaining higher photosynthesis, enhancing antioxidant activity to scavenge excess reactive oxygen species (ROS) ( Xu et al, 2016 ; Lu J. et al, 2022 ; Luan et al, 2022 ), but information regarding the molecular mechanism of grafting in increasing cold tolerance remains largely unknown. In this study, we found that cucumber seedlings grafted onto figleaf gourd significantly increased the tolerance to cold stress through promoting the accumulation of ABA to induce the expression of WRKY41 and WRKY46 , which further activated the expression of miR396b-5b to target cleavage of TPR .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that grafting in vegetables can significantly reduce diseases and environmental risks, especially in successive cropping systems [ 8 ]. In Cucurbitaceae family, pumpkins are used as rootstocks to enhance cold tolerance in cucumber seedlings by boosting the phenylpropanoid metabolism and phytohormones synthesis [ 9 ]. The use of resistant rootstocks in Rosaceae family reveals high resistance of apple scions to apple specific replant disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Si affects a variety of plant physiological activities, including photosynthetic rate, stomatal conductance, water use efficiency, stomatal size and number, transpiration rate, and the hydraulic conductance of roots in many crops [33,34]. The ameliorative effect of Si against freezing has been reported in numerous crops, including grapes [35], mangoes [36], cucumber [37], tomato [38], barley [39], wheat [40], alfalfa [41] and turfgrass [42]. Potassium (K) is another major element in plants that plays an important role in mitigating different abiotic stresses such as drought, heat, and cold [43,44].…”
Section: Introductionmentioning
confidence: 99%